Optimasi Net Working Capital dalam Meningkatkan Perputaran Modal Kerja pada Pt. Sidomuncul - Mukafich, Muchammad Dichyah; Pratama, Baihaqi Nendia (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This study aims to analyze and optimize net working capital to improve working capital turnover at PT. Sidomuncul, an Islamic company in Indonesia operating in the herbal and traditional medicine industry. The method used is quantitative descriptive analysis, utilizing secondary data from the company’s financial reports for the years 2019–2023. The findings indicate that optimal management of net working capital, including the regulation of current assets and current liabilities, has a positive impact on the efficiency of working capital turnover. Implementing appropriate working capital management policies can enhance the company’s financial performance while supporting long-term liquidity stability and profitability.